Analysis of MTb Rapid Molecular Test Performance Towards Microscopical Acid Fast Bacilli Examination at Labuang Baji General Hospital - Ummul Khair; Nursin Abd Kadir; Benny Rusli (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Tuberculosis (TB) is a global health problem, which is the third leading cause of death of all infectious diseases aroundthe world, included Indonesia. Acid Fast Bacilli (AFB) smear and rapid molecular assay for Mycobacterium tuberculosis (MTB)are the old and new examinations required for MTB laboratory diagnosis. This study aimed to compare the performance ofMTB rapid molecular assay and AFB smear in diagnosis and screening for TB patients. This observational retrospective studyused a cross-sectional approach, with a purposive sampling technique of 559 patients with suspected TB in Labuang BajiHospital, Makassar. This study was conducted from March 2019 to June 2019 by taking data from medical records fromJanuary 2018 to December 2018 at Labuang Baji Hospital, Makassar. Three hundred and forty-nine subjects were males(62.4%), and 210 subjects were females (37.6%). This study revealed sensitivity and specificity of 98.57% and 84.96%,respectively for MTB rapid molecular assay, and 68.65% and 99.44%, respectively for AFB smear, this shows that MTB rapidmolecular assay was superior to AFB smear in diagnosing TB patients.